PENGEMBANGAN KOMIK DIGITAL BERBASIS FLIPBOOK TENTANG SIKLUS AIR PADA PEMBELAJARAN IPA KELAS V SD - Zhabrina Alintia; Marini, Arita; Hadi, Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to create a flipbook-based digital comic about the water cycle that is suitable for fifth-grade elementary school students, meets validity criteria, and is appropriate for use in science education. Students’ lack of understanding of the abstract concept of the water cycle and the limited availability of innovative learning media were the primary reasons for conducting this study. The method applied in this study is Research and Development (R&D) following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). For data collection, instruments used included validation sheets from media experts and content experts, as well as a student response questionnaire using a Likert scale. The validation results showed that the media expert’s assessment reached 97%, the content expert’s 90%, while student feedback scored 94%, and all fell into the “Highly Valid” category. The developed media combines engaging digital comic narratives with interactive features of a platform-based flipbook. This final product consists of twelve comic pages covering discussions on evaporation, condensation, precipitation, infiltration, and transpiration in a contextual and visual manner. The conclusion of this study states that flipbook-based digital comics are a suitable science learning medium for water cycle material for fifth-grade elementary school students and are capable of increasing student motivation and conceptual understanding.